Policy Reform in Viet Nam and the Asian Development Bank's State-Owned Enterprise Reform and Corporate Governance Program Loan - George Abonyi (Asian Development Bank (ADB), 2005)
This paper presents a case study of the Asian Development Bank's StateOwned Enterprise (SOE) Reform and Corporate Governance Program Loan that was aimed at supporting fundamental and sensitive reforms in Viet Nam's transition. It examines the context of SOE reform involving Viet Nam's unique, domestically driven process that shapes policy decisions; the design of the Program; and key issues related to implementation and sustainability of selected core reform measures. The purpose is to draw lessons that can assist in better understanding the policy reform process in order to lead to the more effective preparation and implementation of programs supporting such reforms. In order to help structure the case study, a framework is introduced for the analysis of the political economy dimension of policy reform. This framework is proposed as a useful general tool both for the ex post understanding the political economy dimension of policy reform, as well as an analytic tool for assisting in the ex ante design of specific policy reform programs and related policy-based lending.
hdl:11540/1901
Keywords: 330; Wirtschaftsreform; Öffentliches Unternehmen; Privatisierung; Corporate Governance; Entwicklungsbank; Entwicklungsplanung; Kritik; Vietnam